1986
DOI: 10.1016/s0022-5347(17)45933-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Scrotal Hypothermia: Results in 90 Infertile Couples

Abstract: We studied the use of a testicular hypothermia device worn daily for at least 16 weeks in 64 men with subfertile semen and elevated testicular temperature, who had had an infertile marriage for 2 or more years in which the wife was judged fertile. Improvement in 1 or more semen parameters was seen in 42 patients (65.6 per cent). Semen analysis was converted into the motile oval index, a numerical value representing the count, motility and normal morphology. The motile oval index helps to predict pregnancy outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

1990
1990
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
0
20
0
2
Order By: Relevance
“…As another mode of scrotal cooling, repeated cold washings have been recommended (Davidson, 1954), but pertinent studies are missing. To date, only an evaporative cooling device for reduction of scrotal temperature has found its way into daily practice (Zorgniotti et al. , 1980, 1982, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As another mode of scrotal cooling, repeated cold washings have been recommended (Davidson, 1954), but pertinent studies are missing. To date, only an evaporative cooling device for reduction of scrotal temperature has found its way into daily practice (Zorgniotti et al. , 1980, 1982, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the resultant humid environment its application time is limited and only recommended during daytime to allow regeneration of the scrotal skin at night. Among 64 study patients (infertility for at least 2 years, normal gynaecological findings in the female partner) who had worn the cooling device for a minimum of 16 weeks, semen quality was improved in 65.6% and pregnancy occurred in 26.6% cases (Zorgniotti et al. , 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wright et al [13] reported a decrease in testicular temperature after varicocelectomy in infertile men. There are many studies that report about the adverse effects hypothermia and hyperthermia have on spermatogenesis [14][15][16]. Mulcahy [14] reported that scrotal cooling might have a positive effect on improving semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…In der Untersuchung von FigaTalamanca et al [9] [69], zeigte sich in 65,6% eine Spermiogrammverbesserung, und in 26,6% trat eine Schwangerschaft ein. Die Compliance der Patienten betrug insgesamt jedoch lediglich 46%.…”
Section: Autofahrtunclassified